Eastern Catholic Churches in the USA: Problems of the Past, Challenges and Present Promises for the Future - Kimes, John Paul ca. 21. Jh. (Il CCEO - strumento per il futuro delle Chiese orientali cattoliche, 2017)
Vgl. cc. 29C; 390 CCEO